Perceptions Of Selected Heterogeneous Primary School Heads Toward Continuous Quality Improvement (CQI) In The School Strategic Planning - Wan Suraya Binti Wan Nik (Prosiding International conference on Information Technology and Business (ICITB), 2017)
In education today, school heads rely on strategic planning to prepare and manage the school’s academic excellence goals. The study employed a, qualitative longitudinal trend approach investigating the perceptions of the selected heterogeneous primary school Heads in Malaysia toward continuous quality improvement (CQI) in the school strategic planning (SSP) in sustaining quality education. The study involved a one-to-one interview with the selected heterogeneous primary school Headmaster and Head- mistresses in thirteen schools, i.e., four from the northern region of Peninsular Malaysia and nine in the Klang Valley area. The analysis of documents and on-site participant observation accompanied the unstructured face-to-face interview with the respondents. A conceptual framework was designed and applied to the interview responses. The finding of the study indicated that CQI is not a new concept but was already in the school management systems structure known as added-value. As such CQI can be put into practice in the school immediately since the similarities with SSP carried out in the school is very apparent. As a result, six themes emerge from the SSP, namely, 1) Effective Planning Methodology, 2) School Vision and Mission, 3) Culture, Climate and Change, 4) Strategic Outcomes (specifically the school programs), 5) Supportive Leadership, and 6) Broad Stakeholder Buy-in or the involvement of not only the parents, the community but also the students and the school. And the four themes emerge from CQI, namely: 1) Planning and Process, 2) Staffing, 3) Data Management, and 4) Leading. The SSP will act as a compass to direct CQI in the school improvement plan that will bring in students’ academic excellence, high performance school status (HPS) and internationalization contact.  Keywords :Continuous Quality Improvement (CQI), High Performance School (HPS), Heterogeneous Primary School Heads, and Added-Value.